SCHOOL BUDGET NEEDS ASSESSMENT: MULTI-SITES STUDY AT MALANG PUBLIC JUNIOR HIGH SCHOOLS - Sutrisno (re-JIEM (Research Journal of Islamic Education Management), 2023)
This study aims to examine more deeply and find supporting factors related to the need for assessment funding in three public junior high schools in Malang city. In addition, this study also aims to analyze what dimensions are very supportive in the financing assessment process within the institution. This article uses a qualitative research type with a multi-site and descriptive approach to reveal some of these dimensions. Meanwhile, the techniques used in extracting data related to the research theme are in-depth interview techniques, participant observation, and documentation techniques. After going through data mining techniques to obtain information, the researchers found that five main things became successful in assessing school financing needs. First, identify the urgency of allocating absorbed education funding. Second, policy analysis in determining the main priority elements of education financing must be considered so that it is right on target and under the vision and mission of the institution. Third, being able to assess and identify sources that generate funding for education. Fourth, agencies and stakeholders involve the community in the education design and financing process.